Optimizing colour resolusion in 3D model and animation for fast rendering time between PC and Macintosh - Ismail, Azizan (2003)
This project studied whether the optimizing of colour resolution for the non-photorealistic 3D model and animation can make the rendering process becomes faster than before. 130 frames of short and simple 3D animation were tested. Four types of colour resolution in three categories of screen resolution was applied to the 3D animation, and the result shows that the screen resolution give more impact to the rendering process time compare to the colour resolution. This project also present a comparative study between PC-based and Macintosh-based in the 3D model and animation rendering process. The same 3D animation was tested through the two different platforms which has quitesimilar in terms of performance and the result shows that Macintosh-based perform better that PC-based in all rendering processes